2018
DOI: 10.1194/jlr.m081323
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral organoids derived from Sandhoff disease-induced pluripotent stem cells exhibit impaired neurodifferentiation

Abstract: Sandhoff disease, one of the GM2 gangliosidoses, is a lysosomal storage disorder characterized by the absence of β-hexosaminidase A and B activity and the concomitant lysosomal accumulation of its substrate, GM2 ganglioside. It features catastrophic neurodegeneration and death in early childhood. How the lysosomal accumulation of ganglioside might affect the early development of the nervous system is not understood. Recently, cerebral organoids derived from induced pluripotent stem (iPS) cells have illuminated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 69 publications
1
67
0
Order By: Relevance
“…Analysis of hexb −/− mouse fetal neuronal stem cells (NSCs), also called radial glia, revealed a more frequent differentiation towards the astrocyte lineage rather than neurons, indicating abnormal differentiation of brain cells (Ogawa et al, ). SD patient IPS cell‐derived organoids also showed aberrant neuronal differentiation (Allende et al, ). These studies suggest that HEXB deficiency could intrinsically affect neuronal differentiation and induce increased astrocyte numbers, which could be an initiating event in the pathogenesis of SD.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of hexb −/− mouse fetal neuronal stem cells (NSCs), also called radial glia, revealed a more frequent differentiation towards the astrocyte lineage rather than neurons, indicating abnormal differentiation of brain cells (Ogawa et al, ). SD patient IPS cell‐derived organoids also showed aberrant neuronal differentiation (Allende et al, ). These studies suggest that HEXB deficiency could intrinsically affect neuronal differentiation and induce increased astrocyte numbers, which could be an initiating event in the pathogenesis of SD.…”
Section: Introductionmentioning
confidence: 99%
“…Human iPSCs have been differentiated into neurons and/or glial cells to model the neural defects associated to several lysosomal storage diseases (LSDs) including mucopolysaccharidosis (Bayó-Puxan et al, 2018;Canals et al, 2015;Kobolák et al, 2019;Lemonnier et al, 2011;Vallejo-Diez et al, 2018), Niemann−Pick type C (Maetzel et al, 2014;Ordoñez and Steele, 2016;Trilck et al, 2013;Yu et al, 2014), Pompe disease (Higuchi et al, 2014), Gaucher disease (Panicker et al, 2012;Sun et al, 2015;Tiscornia et al, 2013), GM1 and GM2 gangliosidosis (Son et al, 2015) (Allende et al, 2018), NCL (Lojewski et al, 2014), and MLD (Frati et al, 2018;Meneghini et al, 2017). To our knowledge this is the first report describing a human iPSC-based neural model of GLD.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a cerebral SD organoid model, generated from patient-derived iPS cells, has been an interesting approximation to the discovery of novel implications of GM2 accumulation [ 67 ]. In this context, recent findings have described that impaired Hex activity promotes an increase in the size of the cerebral organoids, which was corrected after transduction of HEXA and HEXB cDNAs by using adeno-associated virus (AAV) vectors [ 68 ]. In agreement with these results, and using HEXB deficient zebrafish embryos, Kuil et al, 2019 found an increase in the lysosomal speckles in radial glia [ 69 ], which are progenitor cells able to difference in neurons, astrocytes, and oligodendrocytes [ 70 ].…”
Section: Physiopathology Of Gm2 Gangliosidosesmentioning
confidence: 99%